2019
DOI: 10.3233/jad-181171
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Proteome Profile in AβPP/PS1 Mice Hippocampus, Medial Prefrontal Cortex, and Striatum by Palm Oil Derived Tocotrienol-Rich Fraction

Abstract: Tocotrienol-rich fraction (TRF) is a mixture of vitamin E analogs derived from palm oil. We previously demonstrated that supplementation with TRF improved cognitive function and modulated amyloid pathology in A␤PP/PS1 mice brains. The current study was designed to examine proteomic profiles underlying the therapeutic effect of TRF in the brain. Proteomic analyses were performed on samples of hippocampus, medial prefrontal cortex (mPFC), and striatum using liquid chromatography coupled to Q Exactive HF Orbitrap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 76 publications
0
21
0
Order By: Relevance
“…Thus, 12-LOX inhibition protects Aβ-induced toxicity in the corticol neurons ( 82 ). The reduction in receptor-type tyrosine-protein phosphatase alpha (PTPRA) protein expression by TRF, as shown by Hamezah et al ( 55 ), further confirm the role of TRFs as a neuroprotective agent ( 55 ) via the inhibition of ERK and c-Src in MAPK pathway in APPswe/PS1 mice. PTPRA is perceived as a crucial mediator for synaptic plasticity and neuronal migration and association with memory.…”
Section: Therapeutic Mechanisms Of Tocotrienolsmentioning
confidence: 60%
See 1 more Smart Citation
“…Thus, 12-LOX inhibition protects Aβ-induced toxicity in the corticol neurons ( 82 ). The reduction in receptor-type tyrosine-protein phosphatase alpha (PTPRA) protein expression by TRF, as shown by Hamezah et al ( 55 ), further confirm the role of TRFs as a neuroprotective agent ( 55 ) via the inhibition of ERK and c-Src in MAPK pathway in APPswe/PS1 mice. PTPRA is perceived as a crucial mediator for synaptic plasticity and neuronal migration and association with memory.…”
Section: Therapeutic Mechanisms Of Tocotrienolsmentioning
confidence: 60%
“…This has been illustrated in Figure 2 which refers to the mechanisms of action of T3s in AD. Similarly, Hamezah et al ( 55 ) noticed a decrease of APP in the hippocampus of APPswe/PS1 mice treated with T3s-rich fraction (TRF). In addition, TRF hinders the formation of Aβ fibrils and oligomers in a cell-free assay, and decreases the accumulation of Aβ in the hippocampus and pre-frontal cortex of AβPP/PS1 mice ( 55 ).…”
Section: Therapeutic Mechanisms Of Tocotrienolsmentioning
confidence: 85%
“…Permutation-based analysis revealed 1537 DE proteins (FDR p < 0.050), of which 392 were mapped onto the GSMN and therefore constituted the allmapped AD proteomics dataset. DE proteins from two additional studies (Palomino-Alonso et al 2017;Hamezah et al 2019) failed to reach statistical significance upon FDR correction and thus these datasets were removed from further analysis.…”
Section: De Analysis Of Mapped Ad Mouse Transcriptomics and Proteomics Datamentioning
confidence: 99%
“… Vitamin E A quantitative model based on plasma protein abundances is reported to predict plasma α-tocopherol status, potentiating the development of an inexpensive assay to detect α-tocopherol deficiency [ 185 ]. A study of a mouse model of Alzheimer’s disease reports treatment with the tocotrienol-rich fraction of palm oil reduces the abundance of amyloid beta A4 protein, the primary component of amyloid plaques, in hippocampi [ 186 ]. Vitamin K A quantitative model based on five plasma protein abundances is reported to predict vitamin K deficiency with moderate accuracy [ 187 ].…”
Section: Vitamin Regulation Of Tissue Proteomesmentioning
confidence: 99%
“…An orbitrap-based study of hippocampi, medial prefrontal cortices, and striata tissue in a mouse model of Alzheimer's disease reports administration of a tocotrienol-rich fraction of palm oil down-regulates hippocampi expression of the amyloid beta A4 protein ( APP ). Amyloid beta A4 is the principle component of amyloid plaques characteristic of Alzheimer's disease [ 186 ]. In a QTOF-based study of rabbit aortae, vitamin E supplementation is reported to impact protein abundances including the apolipoprotein, APOA1 , and several related to oxidation/reduction processes [ 206 ].…”
Section: Vitamin Regulation Of Tissue Proteomesmentioning
confidence: 99%